Plan B 2.0 : Rescuing A Planet Under Stress and a Civilization in Trouble - Brown, Lester R. (Lester Russell), 1934- (New York W.W. Norton, 2006)
Brown is president of the Washington, D.C.-based Earth Policy Institute, an organization dedicated to building an eco-economy, and has 50 years of experience working with agricultural and environmental issues. He presents an updated and expanded edition of his 2003 text proposing a new path toward an economy that can sustain economic progress.
Keywords: Natural resources--Management -- Economic development--Environmental aspects -- Environmental policy--Economic aspects